Decoding Inflation and Unemployment: Exploring the Phillips Curve’s Insights on Short-Term and Long-Term Economic Dynamics - Irwan Adimas Ganda Saputra; Waspodo Tjipto Subroto; Norida Candra Sakti; Angga Martha Mahendra (International Journal of Economics and Management Sciences, 2024)
The purpose of this study is to analyse the short-term and long-term economic dynamics based on the Phillips Curve regarding the relationship between inflation and unemployment. The analysis results show that there is an inverse relationship between inflation and unemployment when viewed from the Phillips Curve model in the short-term. The concept of the Natural Rate of Unemployment (NRU) and the Non-Rapid Inflationary Unemployment Rate (NAIRU) emphasizes that the relationship between inflation and unemployment in the long term will weaken due to people's inflation expectations. The results of the study also show that globalization and rapid technological developments are increasingly blurring the traditional relationship between inflation and unemployment, and the importance of adaptive monetary and fiscal policies. The results of this study provide insight for policymakers to formulate more effective strategies to manage inflation and unemployment.